Applications of gene-based technologies for improving animal production and health in developing countries - Makkar, Harinder P. S.; Viljoen, Gerrit J.; Joint FAO/IAEA Division of Nuclear Techniques in Food and Agriculture; Food and Agriculture Organization of the United Nations. Animal Production and Health Division (Dordrecht, The Netherlands : Springer, 2005)
28